2018
DOI: 10.1002/cam4.1585
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use patterns and reasons for use among smokers recently diagnosed with cancer

Abstract: Many patients with cancer use electronic cigarettes (e‐cigarettes), yet little is known about patterns and reasons for use. Using cross‐sectional baseline data from a randomized controlled trial, we aimed to describe prevalence and correlates of e‐cigarette use, frequency of use, and reasons for use among smokers recently diagnosed with cancer. Participants (n = 302) included adults (age ≥18 years) recently diagnosed with varied cancer types who smoked ≥1 cigarette within the past 30‐d from two US academic med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…Yet the provision of perioperative cessation support by clinicians is negatively affected by factors such as the lack of hospital onsite cessation staff and resources, clinicians’ inadequate knowledge of available cessation services, and patients’ prior failed quit attempts with cessation pharmacotherapy [ 7 , 8 ]. The need for patients with coronary artery disease and lung cancer to explore different and novel methods to reduce or eliminate their tobacco use, has given rise to an increased number of patient-clinician discussions about electronic cigarettes [ 9 , 10 , 11 ]. This has led to a similar rise in studies exploring how clinicians involved in the care of patients with such tobacco-induced diseases, interact with their patients around this topic [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the provision of perioperative cessation support by clinicians is negatively affected by factors such as the lack of hospital onsite cessation staff and resources, clinicians’ inadequate knowledge of available cessation services, and patients’ prior failed quit attempts with cessation pharmacotherapy [ 7 , 8 ]. The need for patients with coronary artery disease and lung cancer to explore different and novel methods to reduce or eliminate their tobacco use, has given rise to an increased number of patient-clinician discussions about electronic cigarettes [ 9 , 10 , 11 ]. This has led to a similar rise in studies exploring how clinicians involved in the care of patients with such tobacco-induced diseases, interact with their patients around this topic [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The following demographic characteristics were included in the analysis: age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), and 55 years old or older), sex (male or female), race/ethnicity (non-Hispanic white, non-Hispanic black, Hispanic, or non-Hispanic other races), poverty status (<100% of poverty guideline, 100%-199% of poverty guideline, and ⩾200% of poverty guideline), education level (less than high school, high school graduate or equivalent, some college [no degree] or associate degree, bachelor's degree, or advanced degree), residential region (Northeast, Midwest, South, West), and other tobacco product use ("Yes" or "No"). The poverty income guideline was based on the 2015 poverty guidelines for the 48 contiguous states and the District of Columbia.…”
Section: Methodsmentioning
confidence: 99%
“… 23 Among samples of cancer patients who smoked cigarettes, about 6.5% to 19% reported current e-cigarette use. 24 , 25 Moreover, a cross-sectional U.S. study among cancer patients at the Seattle Cancer Care Alliance found that 2.8% of those with a history of cancer reported current e-cigarette use, which was lower than among the general population. 26 For marijuana use, Pergam et al 27 found that in a state where recreational marijuana use was legal, past-year and past-month prevalences were 24% and 21%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…International research shows that inadequate access to cessation support can contribute to hospitalised patients’ interest in using e-cigarettes to help quit smoking 11 . In view of the need to reduce the harm caused by tobacco use in patients with cancer or CAD, and the recurrence of primary disease and development of secondary disease, studies have shown that e-cigarettes can address a number of behavioural and psychosocial factors contributing to relapse 12 and are being used to reduce or quit smoking 13-15 , reduce the harm of tobacco use 16 , and reduce nicotine cravings 17 . In Australia, smoking rates are low, yet smoking prevalence and the incidence of lung cancer and CAD is higher among older, disadvantaged, or lower socioeconomic groups 18-20 .…”
Section: Introductionmentioning
confidence: 99%